2016
DOI: 10.1002/ps.4437
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance and size assortative mating in females of the maize weevil (Sitophilus zeamais)

Abstract: Susceptible female weevils prefer larger (and heavier) males to mate, a trait associated with deltamethrin resistance, favouring the maintenance and spread of the resistant phenotype in the population. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…When measuring specific components, a general trend is less clear. In general, more studies found a cost in some reproductive (about 64%) and developmental (about 63%) component, but fewer saw a cost due to longevity (about 47%) or body size (about 43%), and none have reported a cost due to sex ratio [3,27,[30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Part of this variation is likely a result of the different mutations and mechanisms (and their combinations) being tested, since these are likely to confer different types of fitness costs.…”
Section: Introductionmentioning
confidence: 99%
“…When measuring specific components, a general trend is less clear. In general, more studies found a cost in some reproductive (about 64%) and developmental (about 63%) component, but fewer saw a cost due to longevity (about 47%) or body size (about 43%), and none have reported a cost due to sex ratio [3,27,[30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Part of this variation is likely a result of the different mutations and mechanisms (and their combinations) being tested, since these are likely to confer different types of fitness costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, these compounds were reported to be highly toxic to the environment and humans, which has led to the search for alternative non-chemical methods of control (e.g., heat treatments and entomopathogenic fungi) and for more environmentally friendly insecticides (e.g., plant essential oils and entomotoxic proteins) [9][10][11][12]. In addition, there are reports on the insecticidal-resistant populations of S. zeamais exposed to selective pressures under laboratory conditions or found directly in the field [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these environments may select for high-resistance, reducing the fre- , 2009). However, it is important to note that although herbicide treatment would be expected to promote strong assortative mating (Cordeiro et al, 2017;Doebeli, 1996) between high-resistance individuals, in the absence of glyphosate stress intermating between low-and high-resistance individuals is expected. Therefore, low-resistance individuals would be predicted to decrease in frequency over time, unless differences in phenology (Baucom, 2019;Bonner et al, 2019;Winterer & Weis, 2004) between low-and high-resistance phenotypes existed.…”
Section: Maintenance Of Variation In Phenotypic Glyphosate Resistancementioning
confidence: 99%